Assessment of inhibitive assay for insecticides using acetylcholinesterase from Puntius schwanenfeldii - Mohd Khalizan Sabullah; Mohd Ezuan Khayat (Hibiscus Publisher, 2015)
In this study, the substrate specificity and the inhibition kinetics of various types of insecticides to the acetylcholinesterase (AChE) from a local fish; Puntius schwanenfeldii were investigated. The substrate specificity determination was done using three thiocholine substrates, which were ATC, PTC and BTC. The results showed that he partially purified cholinesterase from Puntius schwanenfeldii that preferred ATC is a true AChE. The Km and Vmax values of AChE for these substrates were 16.61 mmol and 286.5 U/mg for ATC, 19.92 mmol and 245.3 U/mg for PTC, and 48.64 mmol and 219.6 U/mg for BTC, respectively. The IC50 values for the carbamates bendiocarb, carbaryl, propoxur, carbofuran and methomyl were 0.838, 7.045, 29.441, 1.411 and 8.335 mg/L, respectively, which were comparable to the IC50 values for carbamates from several AChE from fish.